I see you - Genhart, Michael (Magination Press, 2017)
"A wordless picture book that depicts a homeless woman who is not seen by all the life around her, except by a little boy. Ultimately, in a gesture of compassion, this boy approaches this woman, in an exchange where he sees her and she experiences being seen"--